Peningkatan Penanggulangan Terorisme Melalui Mekanisme Kerjasama Indonesia Dan Australia Pada Era Joko Widodo (2014-2019) - Simanjuntak, Romulo (Interdependence Journal of International Studies, 2020)
Terrorism is an issue that is felt by almost all countries in the world. The activities of non-state actors that threaten the security of a country are the main focus of eradication and cooperation between countries. One of the ways to eradicate terrorism regularly is cooperation between Indonesia and Australia. This collaboration then experienced an increase during President Joko Widodo's first period (2014-2019). The Bali Bombing incident was an important momentum for Australia to come together in the fight against terrorism in Indonesia. One of the collaborations that took place between Indonesia and Australia was the cooperation in closing accounts of terrorist groups through a collaboration called AUSTRAC. The purpose of this research is to find out the increased cooperation between Indonesia and Australia in the fight against terrorism in the Joko Widodo era in 2014-2019. The method used in this research is descriptive qualitative research method with literature study. As for some of the positive results found from this collaboration are such as the success of tracking and freezing the flow of terrorist funds in 2017 and the occurrence of a decline in the Global Terrorism Index in 2017. Through this collaboration, the two countries then try to widen cooperation on aspects of prevention and mitigation at a later time.